Helicobacter pylori infection in healthy people: a dynamic process?. Issue 4 (April 1991) - Meyer, B; Werth, B; Beglinger, C; Dill, S; Drewe, J; Vischer, W A; Eggers, R H; Bauer, F E; Stalder, G A
Abstract : Epidemiological studies using serological tests have shown that a large proportion of healthy people have antibodies against Helicobacter pylori (anti-Hp). It is uncertain whether the presence of anti-Hp indicates active infection or only past exposure to the micro-organism. In this study we determined anti-Hp with a specific enzyme linked immunosorbent assay in 100 healthy volunteers who were at the same time investigated for active H pylori infection by means of the 13C-urea breath test. Forty nine per cent had a high anti-Hp titre, but only 24% had active H pylori infection. Our study suggests that a considerable number of healthy people previously infected with H pylori have spontaneously eliminated this microorganism. We suggest that the inability of ulcer patients to eliminate H pylori may be important in the pathogenesis of peptic ulcer disease.